Evaluation of the genotoxic and antigenotoxic potential of Brassica oleracea L. var. acephala D.C. in different cells of mice - Martini Goncalves, Alvaro Luiz [UNESP]; Lemos, Marivane; Niero, Rivaldo; de Andrade, Sergio Faloni; Maistro, Edson Luis [UNESP] (Elsevier B.V., 2012)
Ethnopharmacological relevance: Brassica oleracea L var. acephala D.C. has been extensively used in Brazilian traditional medicine to treat gastric ulcer.Aim of the study: This study was conducted to evaluate the in vivo genotoxic and/or antigenotoxic potential of a Brassica oleraceae hydroalcoholic extract obtained from the leaves, in different cells of mice.Materials and methods: Analyses were performed using the comet assay, on leukocytes (collected 4 and 24 h after treatment), liver, brain, bone marrow and testicular cells (collected 24 h after treatment), and using the micronucleus test (MN) in bone marrow cells. Eight groups of albino Swiss mice were treated (N=6): control (C), positive control (doxorubicin 80 mg/kg (DXR)), and six experimental groups, which received 500, 1000 and 2000 mg/kg of Brassica oleraceae extract alone by gavage, while a further three groups received the same doses plus DXR (80 mg/kg). We calculated the damage scores, and their averages were compared by ANOVA followed by the Tukey test for multiple comparisons.Results: The results demonstrated that none of the tested doses of Brassica oleraceae extract showed genotoxic effects by the comet assay, or clastogenic effects by the MN test. on the other hand, for all cells evaluated, the three tested doses of the Brassica extract promoted inhibition of DNA damage induced by DXR.Conclusions: Under our experimental conditions, Brassica oleraceae leaf extract showed no genotoxic or clastogenic effects in different cells of mice. However, it did show a significant decrease in DNA damage induced by doxorubicin. It is suggested that the antigenotoxic properties of this extract may be of great pharmacological importance, and may be beneficial for cancer prevention. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Brassica oleraceae; Comet assay; Micronucleus test; Antigenotoxic effects